Strategies to reduce corticosteroid-related adverse events in asthma. Issue 1 (February 2019) - Heffler, Enrico; Bagnasco, Diego; Canonica, Giorgio W.
Abstract : Purpose of review: Severe asthmatics, despite the chronic use of high inhaled corticosteroids (ICS) doses and frequent intake of systemic corticosteroids, remains clinically and/or functionally uncontrolled. These patients are also often affected by rhinitis or chronic rhinosinusitis requiring frequent use of intranasal corticosteroids. Therefore, severe asthmatics are exposed to an overload of corticosteroids that is frequently associated with relevant and costly adverse events. This clinical problem and the strategies to overcome it are here summarized. Recent findings: Different therapeutic options may help in reducing the corticosteroid load in asthmatics, ranging from allergy immunotherapy (nonsuitable for severe uncontrolled patients), immunosuppressant agents like methotrexate or cyclosporine, novel biologic drugs (mainly anti-IgE, anti-IL5 and anti-IL4-receptor-alpha), and aspirin desensitization (for patients with anti-inflammatory drugs exacerbated respiratory disease). Summary: The evidence of even serious corticosteroid-related adverse events associated with consistent health-care costs, should prompt the entire scientific community and health regulatory authorities to promote actions to increase the use of well tolerated and effective strategies to reduce the corticosteroid need in asthmatics; the most promising option seems to be the add-on use of biologic agents.